Educação integral: um projeto em construção na Escola Municipal Professor Zeferino Vaz - Estevão, Daniel Carlos (2018)
This research is about the implementation process of the integral education project in the School of Comprehensive Education Professor Zeferino Vaz, belonging to the Municipal Teaching Network of Campinas, a city located in the interior of the State of São Paulo, in the period from 2011 to 2017, which from 2014, as Pilot School, started working full time. To do so, it is proposed: After three years of implementation, have the estabilished objectives in the pilot project been successful? Therefore, this research has the general objective of analyzing the implementation and development of the aforementioned project, with a view to understanding, to what extent, the same one fulfills its greater intent, namely: allowing its students to be able to remain for a while higher in the school and with their fully development. Its specific objectives are to analyze its implementation, focusing on the reorganization of spaces and times; to analyze the relationship between what was proposed in the pilot project and what has been done in the school, and finally, to contribute to the movement and the discussion about integral education in Brazil, especially in Campinas city. In order to meet the objectives we set to ourselves, we use as information gathering procedures: the communicative report and the communicative discussion group, strategies of the Critical Communicative Methodology, questionnaires, reading and analysis of official documents of the Municipal Education Secretariat on the Educational Proposal of integral education schools in Campinas city; documents from the Ministry of Education and Culture and the school being researched, such as the Pedagogical Project, planning and minutes of meetings, as well as the field research, which once gave voice to those involved in the proposal construction process, namely the students and their caregivers, teachers and managers of the educational unit. The main theoretical references used were CAVALIERE (2002, 2007); COELHO (1997, 2004, 2014); FREIRE (1959, 1996); MOLL (2012); RIBEIRO (1985, 1990, 2015) and TEIXEIRA (1959, 2007). The study of this case, showed us that the EEI Prof. Zeferino Vaz, still has important limitations regarding the fulfillment of the project objectives, given the difficulties that have arisen in the implementation of the project and the unfavorable conditions since then. However, it has sought, in a joint effort, ways that lead it to the objectives.